Mengembangkan Pembelajaran Music Pada Anak Tunalaras - Fourman Joyarto Simatupang; Putri Sinpur Sinaga; Helena Turnip (Journal of Cross Knowledge, 2023)
This research aims to develop music learning methods that can increase the participation and understanding of children with hearing impairments. Through a creative and inclusive approach, we designed a program that combines musical elements with teaching methods adapted to the needs of children with hearing impairments. This method aims to facilitate a deeper learning experience and stimulate the development of musical skills, as well as increasing their social and emotional engagement. It is hoped that the results of the research will provide new insights into the development of inclusive and comprehensive music learning for children with hearing impairments. This research focuses on developing a music learning approach that is sensitive to the needs of children with hearing impairments. This Research Method It is also hoped that the results of this research can contribute to the development of music learning methods that are more inclusive and enrich the learning experience of children with hearing impairments